Performance of early weaned calves fed lasalocid - K.L. Anderson; Tiruvoor G. Nagaraja; J.L. Morrill; P.G. Reddy (Kansas Agricultural Experiment Station Research Reports, 1987)
Twenty-two newborn, bull calves were used to determine the effects of lasalocid on growth and feed intake of early-weaned calves from week 1 to 12. Calves were assigned to lasalocid or control groups on day 3. Lasalocid-fed group received lasalocid in milk from day 4 to 7 and in milk and pre-starter from days 7 to 14 and in starter feed from weeks 2 to 12. Lasalocid-fed calves had a significantly higher feed consumption and greater weight gain than calves that did not receive lasalocid. The difference became apparent only after 6 wk of age. Lasalocid appears to be a beneficial feed additive for newborn calves.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Performance; Lasalocid; Feed consumption; Weight gain